HEALTHY LIFE BEHAVIOR IN PREGNANT WOMEN WITH RISK OF PREECLAMPSIA IN THE PHC OF CIPARAY BANDUNG DISTRICT - Hanifa Iqomatulhaq; Ermiati .; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2019)
Poor healthy living behaviors would increase the risk of pregnant women getting preeclampsia. Healthy living behavior prevents the occurrence of preeclampsia. This study aimed to analyze healthy behavior in pregnant women with a risk of preeclampsia in the work area of Ciparay Health Center, Bandung Regency. The research method used was quantitative descriptive. The population in this study were 36 pregnant women with a risk of preeclampsia who were selected using the total sampling technique. This study used a questionnaire instrument modified from HPLP II with a valid test of 0.494-0.864 and the value of Cronbach's alpha 0.950. This instrument had an average range of scores from 1-4 with a mean value of 3.11. Healthy living behavior was considered high if the average score was ≥ 3.11 and was considered low if the score was <3.11. The study was conducted on 7-16 October 2018. The results of this study indicated that the healthy behavior of pregnant women with a risk of preeclampsia in the Ciparay Community Health Center work area was in the high category of 20 respondents (55.6%). Also obtained the lowest dimensions were interpersonal relationships, physical activity, and nutrition. The conclusion was pregnant women with the risk of preeclampsia have a poor healthy living behavior, especially in the dimensions of physical activity and nutrition. Therefore, a strategy or program is needed to improve the healthy behavior of pregnant women at the risk of preeclampsia.Keywords: healthy living behavior, pregnant women, the risk of preeclampsia.